Aluminium Alloys New Trends in Fabrication and Applications - Ahmad, Zaki (IntechOpen, 2012)
Aluminium alloys have undergone a dramatic transformation in areas of extrusion, machining, welding, heat treatment, structural changes, created by ultra fine particles and enhanced corrosion resistance. Hence, these alloys have made rapid gains in European automotive and space industry. These developments have been described by experts in the book with new data and attractive graphics. The effect of processing parameters, including welding and deep rolling on their performance have been highlighted to alleviate the concerns of manufacturers and designers for new applications. The novel role of aluminum alloys in photovoltaic cells and concentrated solar power has been comprehensively described in the context of corrosion and the aggressive environment to which they may be exposed. The book is designed to serve as a guide for future innovations and new developments in aluminium alloys.